The Effect of Resist and Assist Torque of Hip Joint Motor-based Gait Assistance Robot on Gait Function in the Elderly - Hyung Gyu Jeon; Kyunghwan Jung; Byungmun Kang; DaeEun Kim; Yun Mook Lim; Kwang Joon Kim; Chang Oh Kim; Hwang-Jae Lee; Kyungrock Kim; Yoon-Myung Kim (Asian Society of Kinesiology, 2022)
OBJECTIVES The purpose of this study was to investigate the effects of assist and resistance torque on the spatiotemporal gait characteristics, and the symmetry and asymmetry of gait using a Gait Enhancing and Motivating System (GEMS) in the elderly. METHODS A cross-sectional and repeated measure design was used. A total of 18 participants (9 males, 9 females; age: 63.5 ± 5.02 years; mass: 64.26 ± 6.87 kg; height: 164.06 ± 7.15 cm) were recruited from a local community, and spatiotemporal gait data were collected with OptoGait system and GEMS. Spatiotemporal gait variables and differences between the dominant and non-dominant legs of these variables were assessed (step length, step time, stance phase, swing phase, single support, load response, pre swing phase, stride time, stride length, double support, cadence, and gait speed). The effects of three modes including normal, assist, and resist modes using GEMS were investigated twice for each participant on a 9-meter walkway. A one-way repeated measure analysis of variance followed by Bonferroni post-hoc tests was conducted. RESULTS The assist mode increased step time, swing phase, stride time and reduced stance phase, pre-swing phase, double support, cadence, and gait speed as compared to normal mode. The resist mode increased stance phase, load response, pre-swing phase, double support, cadence, and reduced step time, swing phase, and stride time. In dominant leg, assist mode showed increased step time and reduced pre-swing phase than normal mode, and greater step time than resist mode (p < 0.05). However, there was no effect of external torque on symmetry and asymmetry between both legs (p > 0.05). CONCLUSIONS The resistance and assist torque of GEMS alter spatiotemporal characteristics during the stance and swing phase of gait in the elderly. However, the resistance torque and assist torque of GEMS did not increase or decrease the gait asymmetry between the dominant and non-dominant legs.